Regesten Kaiser Friedrichs III (1480-1482) Die Urkunden und Briefe des Österreichischen Staatsarchivs in Wien, Abt. Haus-, Hof- und Staatsarchiv: Allgemeine Urkundenreihe, Familienurkunden und Abschriftensammlungen (1480-1482). Bearbeitet von Petra Heinicker und Anne-Katrin Kunde - Kunde, Anne-Katrin; Heinicker, Petra (2020)
This volume lists 222 documents and letters from Emperor Friedrich III. from the Vienna State Archives, which were issued in the years of government 1480-1482 and were aimed at a large number of addressees in the Empire and in the Habsburg lands. They relate to political conflicts, such as the dispute over the new occupation of the Salzburg Erzstuhl, the emperor's disputes with the Hungarian king Matthias Corvinus and the planned appointment of those from Groningen to Reichspotestaten from Friesland, but above all depict the activities and official acts of the Habsburg in his inheritance . The latter shed light on local ownership structures and interdependencies between Frederick III's financial needs. and the chances of social and political integration of its donors.